Analisis pengurangan emisi karbon melalui inovasi perancangan rooftop garden di lingkungan perkotaan - Balqis, Putri; Wulandari, Riski; Zulfandi, Muhammad (Jurnal Teknologi Cerdas, 2024)
Reducing carbon emissions is a crucial undertaking in tackling global climate change. A variety of approaches are used to reduce the increasing carbon emissions caused by industrialization and economic growth, especially in urban areas. A growing trend that could be adopted is the establishment of rooftop gardens in urban areas. This paper seeks to critically examine a range of literature review that specifically investigate the environmental advantages of rooftop gardens, with a particular emphasis on their potential to mitigate carbon emissions. The study was conducted by studying and reviewing diverse sources pertaining to the implementation of rooftop gardens in mitigating carbon emissions. Research in the field of literature indicates that rooftop gardens possess significant capacity to mitigate carbon emissions and effectively address the obstacles posed by climate change. Successful installation of a rooftop garden necessitates meticulous planning and a profound comprehension of environmental and technological aspects. Hence, rooftop gardens offer not only an environmentally friendly alternative, but also yield substantial economic and social advantages. Rooftop gardens enhance CO2 absorption, lower surface temperatures, and decrease building energy needs by improving thermal insulation. In addition to that, this green area also contributes to the enhancement of air quality and urban biodiversity. This review identified numerous designs and best practices that can optimize the ecological and economic advantages of rooftop gardens. The analytical results also indicate the possibility of incorporating rooftop gardens into urban planning, which could serve as a viable approach to reducing climate change and enhancing the urban quality of life.